Impact of Arya Samaj on the Fabric of Indian Society In 19Th Century: Renaissance and Reformation in 19th Century Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Two movements changed the face of Europe andrevolutionized its culture that then conquered the world — Renaissance (thatrevived the long lost treasures of Greek and Latin literature) and Reformation.In India Rishi Dayananda Saraswati is the father of both Renaissance (hebrought to life world's supreme knowledge, the Vedas, with his slogan `Back toVedas) and Reformation ( he sought to rid Hinduism of its massive superstitiouspractices and challenged the authority of the priesthood).